Etiology and risk factors of intracranial hemorrhage and ischemic stroke in young adults. Issue 10 (6th August 2021) - Chen, Chun-Yu; Lin, Po-Tso; Wang, Yun-Huei; Syu, Ruei-Wun; Hsu, Shao-Lun; Chang, Li-Hsin; Tsai, Jui-Yao; Huang, Hui-Chi; Liu, Tzu-Ching; Lin, Chun-Jen; Tang, Chih-Wei; Hsu, Li-Chi; et al.
Abstract : Background: Young stroke incidence has increased worldwide with lifestyle changes. Etiology and risk factors for both ischemic and hemorrhagic stroke in young Asians remain underexplored. Methods: We retrospectively reviewed consecutive acute stroke patients aged 16–45 years admitted to the Taipei Veterans General Hospital between 2009 and 2019 to analyze etiologic subtypes, risk factors, and serial modified Rankin Scale scores for 1 year and compare the age groups of 16–30 and 31–45 years. Results: Among 670 young Taiwanese patients (mean age at onset 37.5 ± 7.0 years; male 65.1%), there were 366 nontraumatic spontaneous hemorrhagic stroke (including 259 intracerebral hemorrhage [ICH] and 107 subarachnoid hemorrhage, SAH), 292 ischemic stroke and 12 cerebral venous thromboses. Notably, ICH was more prevalent in patients aged 16–30 than in those aged 31–45 (54.8% vs 36.8%). Specifically, structural vasculopathy (e.g., arteriovenous malformation, cavernoma) was the most common etiologic subtype in patients aged 16–30 ( p < 0.001), whereas hypertensive ICH was the most common subtype in patients aged 31–45 ( p < 0.001). On the other hand, the top ischemic subtype for both age groups was other determined diseases (e.g., arterial dissection, autoimmune diseases, moyamoya disease, etc.) rather than large artery atherosclerosis. Hyperlipidemia, diabetes, and cigarette smoking were more common risk factors for infarction than ICH. Familial stroke patients whose first- or second-degree relatives had a stroke by age 80 (n = 104, 15.5%) had more infarctions than those without a familial stroke history. In multivariate analyses, initial stroke severity, and infarction type were important predictors of favorable outcomes after 3 months. At the 1-year follow-up, patients with ICH and SAH had worse functional outcomes and survival rates than those with infarction. Conclusion: An aggressive approach to elucidate the etiology of stroke is indicated because structural vasculopathy-induced ICH and other determined infarction are distinctively prevalent in young adults, particularly those aged 16–30.